2013
DOI: 10.1007/s00266-013-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Filler Injections for Tear-Trough Deformity: Injection Technique and High-Frequency Ultrasound Follow-up Evaluation

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“… 63 De Pasquale et al observed that, in the subcutaneous tissue, hyaluronic acid is perceived as a regular, well defined, hypoechoic mass. 64 As different fillers have their own characteristics to HFUS, this may also be useful to differentiate their nature so as to detect possible complications. 61 …”
Section: Applicationsmentioning
confidence: 99%
“… 63 De Pasquale et al observed that, in the subcutaneous tissue, hyaluronic acid is perceived as a regular, well defined, hypoechoic mass. 64 As different fillers have their own characteristics to HFUS, this may also be useful to differentiate their nature so as to detect possible complications. 61 …”
Section: Applicationsmentioning
confidence: 99%
“…Approximately 0.2–0.5 ml was injected at a time per side. This technique created a deep scaffolding that could fill the orbital hollow [6, 7]. …”
Section: Methodsmentioning
confidence: 99%
“…The reported follow-up duration, when mentioned, ranged from 12 months [29] to 5 years [39,69] , with prolonged edema, the Tyndall effect and contour irregularities as the most commonly reported complications, along with diplopia [25] , and xanthelasma-like reactions [53] as a rare occurrence. Complications were also reported in several articles, even if not the focus of the study [13,17,22,28,32,[71][72][73][74][75] , and included two cases of cellulitis and one of migraine [13] .…”
Section: Complicationsmentioning
confidence: 99%
“…Research focused on personal techniques purposed by the authors have been published since 2005. Airan and Born [11] and Kane [12] wrote the first articles ever about this topic, both in 2005; technique refinement and new trends have been published in 2006 [22,23] , 2007 [24,33] , 2011 [16,32,76] , 2012 [26,41,42,66] , 2013 [73] , 2014 [43] , 2015 [48][49][50] , 2016 [27,28] , 2017 [17,52] , 2018 [19,71,74] and 2019 [21] .…”
Section: Techniquementioning
confidence: 99%
See 1 more Smart Citation